Scaling Up Climate-Smart Funding in East and West Africa - Wamicwe, Peter; Burra, Dharani Dhar; Costa, Ciniro; Masika, Daniel; Alarcón, Marina; Grosjean, Godefroy; Newman, Richard; Hientz, Lennhart (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
This info note explores the use of science and technical approaches in improving the typical investment process with regards to investment origination and selection